2004
DOI: 10.1530/eje.0.1510511
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of BMP2 and BMP7 in spermatogonia and Sertoli cell proliferation in the immature mouse

Abstract: Aim: The aim of this study was to determine the action of bone morphogenetic proteins (BMPs) on testicular cell proliferation during early postnatal life, a definite developmental time at which crucial changes in germ cell and Sertoli cell maturation occur. Methods: We investigated the effect of BMP2 and BMP7, two factors which belong to the relatively distant decapentaplegic (DPP) and 60A classes of the large BMP family, upon spermatogonial and Sertoli cell proliferation, and we examined the expression of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 51 publications
4
53
0
Order By: Relevance
“…11a). Following stimulation of Sertoli/ germ cell cocultures with BMP2 and BMP4 at concentrations used in previous studies (Pellegrini et al, 2003;Puglisi et al, 2004), Western blot analysis confirmed that both BMP2 and BMP4 increased SMAD1/5/8 phosphorylation relative to untreated control samples, with an increase in intensity of a band that colocalizes with SMAD5 (Fig. 11b).…”
Section: Immature Sertoli Cells and Spermatogonia Respond To Bmp2 Andsupporting
confidence: 74%
See 2 more Smart Citations
“…11a). Following stimulation of Sertoli/ germ cell cocultures with BMP2 and BMP4 at concentrations used in previous studies (Pellegrini et al, 2003;Puglisi et al, 2004), Western blot analysis confirmed that both BMP2 and BMP4 increased SMAD1/5/8 phosphorylation relative to untreated control samples, with an increase in intensity of a band that colocalizes with SMAD5 (Fig. 11b).…”
Section: Immature Sertoli Cells and Spermatogonia Respond To Bmp2 Andsupporting
confidence: 74%
“…upon, cells of prepubertal testis (Pellegrini et al, 2003;Puglisi et al, 2004), with BMP2 and BMP4 implicated in spermatogonial proliferation and differentiation (Pellegrini et al, 2003;Puglisi et al, 2004) and BMP7 in Sertoli cell proliferation (Puglisi et al, 2004).…”
Section: Immature Sertoli Cells and Spermatogonia Respond To Bmp2 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple ligands in the TGF-β superfamily are thought to play a role in this process, including TGF-β, BMPs, anti-Mullerian hormone (AMH), and GDNF. BMP signaling is required for the specification of primordial germ cells during embryogenesis (30)(31)(32), and contributes, along with GDNF signaling, to the selfrenewal of spermatogonial stem cells (13,14) and the maintenance of spermatogenesis (16). Here we present evidence that alk6/BMPR1B is cell-autonomously required for germ-cell differentiation.…”
Section: Discussionmentioning
confidence: 61%
“…In vitro, exogenous BMP4 appears to drive the differentiation of spermatogonial stem cells from enriched germ-cell cultures (11,12). BMP2 and glial-derived neurotrophic factor (GDNF), also a TGF-β family ligand, have likewise been implicated in the regulation of spermatogonial stem cell self-renewal (13,14). In mouse models, inactivation of BMP8b led to reduced or delayed germ-cell proliferation and differentiation during the first wave of spermatogenesis at puberty, and increased apoptosis of pachytene spermatocytes, leading to reduced fertility in the adult (15).…”
mentioning
confidence: 99%